Relationship Between Family Support and Access to K4 Visits for Pregnant Women at the Merbau Island Health Center, Meranti Islands Regency - Harahap, Juraida Roito; Fatimah, Siti; Permata, Septi Indah (JURNAL IBU DAN ANAK, 2023)
K4 visits are a form of service during pregnancy to get visits by pregnant women with 6 or more contacts with health workers. Based on the data obtained from the report on the achievements of the Merbau Island Health Center activities, the mother's irregularity in carrying out pregnancy checks resulted in the K4 coverage at the Merbau Island Health Center not reaching the Minimum Service Standards (SPM) target in the last 2 years. One of the causes of the low coverage of K4 visits is the displacement of the Old Puskesmas Building to a place far from residential areas and poor road access. The purpose of this study was to determine the relationship between family support and access to K4 visits for pregnant women. This type of research is quantitative with cross sectional methods. The population in this study were third trimester pregnant women with the interpretation of giving birth in March 2022. The sample in this study amounted to 34 pregnant women who were taken by Total Sampling. The data collection instrument used a questionnaire. Data analysis using chi square test. The results of the analysis showed that there was a relationship between family support and access to K4 visits at the Merbau Island Health Center with a p value of 0.000 < 0.05 and a p value of 0.017 < 0.05. It is hoped that this research can be useful for health workers, especially midwives at the Merbau Island Health Center in improving health education about the importance of K4 visits, scheduling prenatal care according to standards and increasing the motivation of pregnant women by involving families in providing support to pregnant women